Analisis Konsumsi Beras di Provinsi Sumatera Barat - Siti Nurul Qomariyati; Gusriati; Herda Gusvita (Fakultas Pertanian, Universitas Ekasakti, 2022)
The purpose of this study was to analyze the development of rice consumption in the province of West Sumatra and to analyze the factors that influence rice consumption in the province of West Sumatra. This research was conducted from April to May 2021. The location determination was done purposively, the data used was secondary data. The basic method used in this research is descriptive analytical method using time series data. The analysis used is trend analysis and multiple linear regression analysis using the SPSS version 20 program. The results show that the equation of the trend line for rice consumption in West Sumatra Province is Y= 100.67-0.86X. The intercept value obtained from the analysis is 100.67 (the average rice consumption in West Sumatra Province over the last 20 years is 100.67 kg/capita/year). The value of the trend coefficient is -0.86 (rice consumption in West Sumatra Province has decreased by 0.86 kg each year). It can be predicted that the consumption of rice in West Sumatra Province in 2025 is 74.01 kg/capita/year. Meanwhile, simultaneously (simultaneously) are the variables of population, education level, rice productivity, per capita income and inflation (sig 0.000 <0.05). The coefficient of determination (R2) in this study was 96.7%, (variables of population, education level, rice productivity, per capita income and inflation contributed 96.7% to rice consumption)